Analisis Yuridis Normatif Klausul Force Majeure dalam Perjanjian Bisnis di Indonesia - Sudjai Sudjai; Didit Darmawan; Muhammad Zufar Afifudin; Gusti Ananda Syalum Saputra; Triyono Meidi Rahman; Akbar Putra Maulana Nur Cahyo (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The concept of force majeure is essential in business agreements in Indonesia, as it regulates the release of contractual obligations that cannot be fulfilled due to events beyond their control such as natural disasters, pandemics, conflicts, or government policies. This study examines force majeure clauses in business agreements in Indonesia from a normative juridical perspective, focusing on the legal framework, its application practices, and its legal implications for contractual certainty. Using normative juridical qualitative methods, data were analyzed from the Civil Code (KUHPerdata) Articles 1244–1245 and 1444–1445, legal doctrine, and literature. The results of the study underlined that the force majeure clause has a strong legal basis in the Civil Code, which exempts the affected party from the obligation of compensation if the failure to perform the obligation is caused by events beyond his control. The application of this clause in the contract allows for the revision, postponement, or termination of a temporary contract, thereby guaranteeing legal certainty and protecting the principles of good faith and contractual fairness. In addition, the formulation of detailed clauses in the contract is crucial to prevent potential legal disputes down the road and ensure fair protection for all parties involved in the business agreement.